2017
DOI: 10.2147/cia.s142538
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment associated with locomotive syndrome in community-dwelling elderly women in Japan

Abstract: In our worldwide aging society, elderly people should maintain cognitive and physical function to help avoid health problems. Dementia is a major brain disease among elderly people, and is caused by cognitive impairment. The locomotive syndrome (LS) refers to a condition in which people require healthcare services because of problems associated with locomotion. The purpose of this study was to determine the association between cognitive impairment and LS. Study participants were 142 healthy elderly female volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Although our results did not theoretically discriminate among the 3 factors completely without cross-loading and residual correlations, it would potentially be able to assist clinical physicians in understanding the concept of LS (pain, movement-related difficulty and psycho-social complication) because these factors fundamentally contribute to the concept of LS and are closely linked with each other. Moreover, previous studies also reported relationships between musculoskeletal pain (Hirano et al, 2014;Iizuka et al, 2015;Imagama et al, 2017;Kimachi et al, 2019), movement-related difficulty or functional decline (Akai et al, 2016;Iwaya et al, 2017;Izawa et al, 2019;Muramoto et al, 2012;Yoshimura et al, 2011), and psycho-social complication (Ikemoto et al, 2016;Nakamura et al, 2017aNakamura et al, , 2017bMaruya et al, 2018) and LS. Thus, it seems reasonable to discriminate among these 3 dimensions when assessing LS during clinical practice.…”
Section: Discussionmentioning
confidence: 87%
“…Although our results did not theoretically discriminate among the 3 factors completely without cross-loading and residual correlations, it would potentially be able to assist clinical physicians in understanding the concept of LS (pain, movement-related difficulty and psycho-social complication) because these factors fundamentally contribute to the concept of LS and are closely linked with each other. Moreover, previous studies also reported relationships between musculoskeletal pain (Hirano et al, 2014;Iizuka et al, 2015;Imagama et al, 2017;Kimachi et al, 2019), movement-related difficulty or functional decline (Akai et al, 2016;Iwaya et al, 2017;Izawa et al, 2019;Muramoto et al, 2012;Yoshimura et al, 2011), and psycho-social complication (Ikemoto et al, 2016;Nakamura et al, 2017aNakamura et al, , 2017bMaruya et al, 2018) and LS. Thus, it seems reasonable to discriminate among these 3 dimensions when assessing LS during clinical practice.…”
Section: Discussionmentioning
confidence: 87%
“…Physiological parameters measured using bioelectrical impedance analysis (Inbody270; Inbody, Tokyo, Japan) with 20 and 1000 kHz frequencies were obtained from the participants' electronic medical records [20]. Participants were instructed to grasp the handles of the analyzer and stand on electrodes in contact with the lower surface of their feet while they were wearing normal indoor clothing without socks or shoes.…”
Section: Assessment Of Body Characteristicsmentioning
confidence: 99%
“…We collected data on physiological parameters obtained using bioelectrical impedance analysis (InBody270; InBody, Tokyo, Japan) at 20 and 1000 kHz frequencies from participants' electronic medical records [29]. Measurements were recorded within 30 seconds by the staff.…”
Section: Body Muscle Massmentioning
confidence: 99%